Własność — zawłaszczanie czy korzystanie? - Tittenbrun, Jacek (Wydział Prawa i Administracji UAM, 1988)
One of basic weaknesses of a great part of conceptions of property formulated in the writings is the inability to define specific economic contents of property. Among others, such is the case of defining property as "appropriation". Those definitions are burdened with "idem per idem" error or they reduce property to the productive labour process. An example of logical and theoretical difficulties resulting from defining property as "appropriation" is the conception of a Soviet economist, J. Kronrod. In another group of definitions appropriation appears as a synonym of "use", which in the author's opinion is the fullest expression of property in the economic sense. However, the use of a different term makes the said synonymity hard to notice. The conception of property defined as "use" may also include the analysis of relationships of junction between means of production and labour, treated by some authors as "definiens" of property. However, in such a case it is necessary to clear the category of junction between means of production and labour of formal- -legal and vague formulations, typical for most of current conceptions.
Property — appropriation or use?